الحل الأمثل لتغذية حمولة من مصادر طاقة متجددة باستخدام الطريقة البسيطة وطريقة تابع العضوية الضبابي - صبيح مسعود (Latakia University Journal -Engineering Sciences Series, 2019)
يعالج هذا البحث موضوع التغذية الكهربائية لقرية نبع الناصرية التي تقع الى الشمال من مدينة تلكلخ بمسافة 10 كم، وإلى جوار سد تل حوش. حمولة القرية تعمل على نوعين من توتر التغذية، توتر متناوب 220 V AC، وتوتر مستمر 24 V DC، تم تغذية هذه الأحمال من خلال مصادر طاقة متجددة(طاقة الرياح والطاقة الشمسية) ومصادر طاقة مساندة (وحدات ديزل ومدخرات) لزيادة موثوقية نظام الطاقة. تهدف هذه الدراسة إلى إيجاد الحل الأمثل لتابع الهدف ممثلا بتابع الكلفة وكقيمة أصغرية، هذا التابع يخضع لمجموعة معادلات قيود تعبر عن الحمولة واستطاعة الخرج لوحدات التوليد. تم إيجاد الحل الأمثل باستخدام الطريقة البسيطة التقليدية، ومن خلال اعتماد قيم متوسطة لسرعة الرياح، والإشعاع الشمسي بحسب بيانات الأرصاد الجوية، ولكن هذه البيانات تتميز بخاصية عدم الدقة وانعدام إمكانية التحديد المسبق. للتخلص من هذا الإشكال عالجنا المسألة باستخدام المنطق الضبابي، استخدام طريقة تابع العضوية للمنطق الضبابي، يجعل قيم بيانات المناخ من إشعاع شمسي وسرعة رياح تتغير بشكل سلس، أو متدرج وهذا يجعل النتائج قريبة جداً الى الواقع العملي، تطبيق المنطق الضبابي في هذه الدراسة يساعد في تحقيق الحجم الاقتصادي لمصادر الطاقة المتجددة وهو يوافق حالة تشغيل أمثل لهذه المصادر عند أقل كلفة ممكنة. This paper addresses the issue of supplying a load to Nabie Alnasriea village which is located 10 [kms] to the north of ( Tal Kalakh) town and Adjoining the dam of (Tal Hush). The load of the village operates on two types of supply voltages: (220 V AC) and (24 V DC), these loads were supplied by renewable energy sources (Wind and solar energy) beside auxiliary energy sources (Diesel Units and batteries) to enforce reliability of the energy system. The objective of this study is to determine the optimum solution for the target function represented by the cost function or as a minimal value, and this function is a subject to a set of constraints equations that represent the load, and the output capacity of the power generating units. The optimum solution was determined by using the simplex traditional method, then through adopting average values for wind velocity and solar radiation according to the meteorology data available, these data however, are lacking certainty and the possibility to be pre-determined. To eliminate this problem, we handled it by using the fuzzy logic, the use of fuzzy membership method will insure reasonable approximation for the climate data variables(like solar radiation and wind velocity). Application of the fuzzy logic in this study will serve to determine the economic volume for the renewable energy sources which conforms to the optimum operation state for these sources at the least cost possible.